Protection of Women in Disaster Emergency Situations; Seven Stages of Participatory Capacity and Vulnerability Analysis - Aprillia, Bunga; Komariyah, Imas; Saleha, Eha (Indonesian Journal of Social Science Research, 2022)
The potential for disasters in Indonesia is quite high, the potential for these disasters can have a greater impact on women and children who are vulnerable groups of people. Disaster risk assessments should consider the vulnerable groups to be in the first place to be discussed. The study needs to be reviewed by looking at existing vulnerabilities and participatory capacities in the community by involving the facilitator team and the community. The seven stages of Oxfam's participatory capacity and vulnerability analysis (PCVA) provide a detailed description of what steps need to be taken to involve the wider community. The seven stages of PCVA start from preparing, collecting secondary data, beginning work with the community, analyzing hazards, prioritizing risk, developing a risk reduction action plan, and putting the action plan into practice. Using qualitative research methods, this study recommends that disaster risk studies that need to be prepared by looking at the perspective of gender sensitivity specially for Indonesia.